The Impact of Project-Based Learning on Students' Collaboration Skills in Secondary Schools - Sappaile, Baso Intang; Hartinah, Galuh; Hendrik, Hendrik; Anshoriyah, Sofiyatul; Sumanik, Ermi Dikta (International Journal of Educational Research Excellence (IJERE), 2025)
The objective of this investigation is to examine the impact of project-based learning on secondary school students' collaborative abilities. This investigation utilizes qualitative research methods and a case study approach. To this end, data were collected via direct observations of students' interactions during the project, in-person interviews with students and teachers to gain insight into their experiences, and an analysis of documents such as project assignments, reports, and students' reflections. Findings from the study demonstrated that the integration of PBL led to substantial advancements in students' collaboration abilities. These enhancements can be categorized into three main aspects: communication skills, teamwork, and problem-solving abilities. The analysis of communication skills revealed that students exhibited an improvement in conveying ideas and attending to others' opinions, indicating enhanced interactive processes. Furthermore, students displayed an enhancement in teamwork, which included effective task allocation and reciprocal assistance in accomplishing shared objectives. Additionally, problem-solving skills exhibited by students demonstrated a marked progression, with students attaining creative and innovative solutions through collaborative efforts. The findings of this study offer significant insights into the merits of incorporating project-based learning methodologies within the secondary school curriculum, with the aim of cultivating critical collaboration skills in students to equip them to confront challenges in their future educational and professional pursuits.The effective integration of this pedagogical approach necessitates comprehensive support from educators in their role as facilitators, along with students' readiness to engage in a more interactive and participatory learning process. Further exploration through research is warranted, focusing on the implementation of this pedagogical approach across diverse contexts and academic levels. Such inquiry would serve to enhance the comprehension and practical implementation of project-based learning strategies in cultivating students' collaborative skills.